Comparing complications in irradiated and non‐irradiated free‐flaps in patients with bilateral immediate breast reconstruction and unilateral post‐mastectomy radiotherapy. Issue 7 (22nd April 2021) - Ly, Catherine L.; Khetpal, Sumun; Heller, Danielle R.; Higgins, Susan A.; Killelea, Brigid; Alperovich, Michael; Avraham, Tomer
Abstract: Background: Numerous studies have evaluated the effect of post‐mastectomy radiotherapy (PMRT) on autologous breast reconstruction, but the variability of PMRT regimens and inadequate controls have made results difficult to interpret. Therefore, in this study, irradiated free‐flaps are compared to non‐irradiated internal controls in patients who underwent immediate bilateral reconstruction followed by unilateral PMRT to better delineate the effect of PMRT. The role of regional nodal irradiation (RNI) is also specifically assessed. Methods: Appropriate patients were identified through retrospective review. Complications such as fat necrosis, fibrosis, infection, delayed healing, and flap loss, as well as revision surgeries, among the irradiated free‐flaps were compared to those on the contralateral non‐irradiated side. Additional analyses were performed to evaluate the effect of patient demographics and treatment characteristics, such as RNI, on complications involving the irradiated free‐flaps. Results: Seventy‐three women were included. There was no significant difference between complication rates for the irradiated and non‐irradiated free‐flaps (39.7% vs. 38.4%, p  = .78), although irradiated free‐flaps were more likely to have fibrosis (17.0% vs. 0.0%; p <  .0001) and multiple complications (9.6% vs. 0.0%; p  = .02). Both groups underwent a similar number of revision surgeries (42.5% vs. 41.1%; p  = .29). Looking at the irradiated free‐flaps, internal mammary node (IMN) irradiation was the only factor predictive of complications (IRR 3.80, CI 1.32–10.97; p  = .01). Conclusions: PMRT may contribute to free‐flap fibrosis, but does not appear to affect the overall risk of complications or revision surgeries. However, additional counseling is warranted if IMN irradiation is likely, as it is potentially associated with increased complications.